Effect of Green Tea Powder on Physicochemical Properties and Glycemic Potential of Sponge Cake. (26th May 2022) - Mashkour, Mana; Azari, Abdolkhalil; Hashemi Shahraki, Masoud; Raeisi, Mojtaba; Ebrahimi, Maryam
Abstract : Green tea powder (GTP) is rich in polyphenolic compounds, most particularly catechins. The effects of partial replacement of flour with GTP (10, 20, and 30%) on physicochemical properties, glycemic potential, and sensory attributes were investigated. Results showed a significant reduction in the moisture content, volume, and porosity of sample cakes with the increase in the GTP levels (P ≤ 0.05 ). The utilization of GTP led to a harder texture and also darker color of sponge cake. The study showed that sponge cakes with good sensory attributes can be produced by the replacement of flour with 10% of GTP. Moreover, the glycemic potential and free radical scavenging activity of sample cakes improved as the GTP replacement increased (P ≤ 0.05 ). GTP at 10% replacement level is recommended as it is very effective in improving the antioxidant properties, sensory attributes, and also glycemic potential.